Exploring factors influencing collaborative knowledge construction in online discussions: student facilitation and quality of initial postings - Ioannou, Andri; Demetriou, Skevi; Mama, Maria (My University, 2014)
Although lots of studies have investigated collaborative knowledge construction in online courses, the factors influencing this process are yet to be fully determined. This study provides quantitative and qualitative types of evidence on how (naturally emerged) student facilitation and quality of initial postings influence collaborative knowledge construction in online discussions. We analyzed the discourse of nine student groups (N = 34) working on a case problem in an online discussion forum. We found that student facilitation was an important contributor to the process. In contrast, the contribution of low-quality postings in early stages of the discussion can jeopardize the process. This work is an attempt to address quality in online learning by helping instructors decide on encouraging student facilitation in online discussions as well as structuring and carefully monitoring the content of initial discussion postings.
Keywords: Collaborative learning; Asynchronous online course; Quality of students’ postings; Quality in online learning